Erratic Climate Change Planning: The Gold Coast’s Alternating Transition - Howes, Michael; Dedekorkut-Howes, Aysin (AESOP, 2019)
Planning the future spatial development of coastal cities is a challenge that has become even more difficult due to the impacts of climate change, governing institutions that were not designed to address such wicked problems, and the reluctance of some right-wing governments to respond. The Gold Coast, Australia, provides a case in point. The city is highly vulnerable to the impacts of climate change having been hard hit by storms, floods, heatwaves, and droughts over decades. The governing system for the region is part of a complex three-tiered hierarchy involving national (Commonwealth), state (Queensland), and local governments (City of Gold Coast). Governments periodically swing between a rightwing Coalition (of the Liberal and National parties) and the left-wing Labor party (sometimes with the support of the Greens party). In the period 2007-2012 all levels of Australian government had started to take the first steps in addressing the challenges posed by the need to adapt to the impacts of climate change. The shift to right-wing governments during the period 2012-15, however, saw many climate plans and policies and plans reversed due to the combined effects of: gaps in the three-tiered system of government; the ideology of the rightwing parties in power; powerful economic interests; electoral politics; fears of legal liability; and, the unique features of the Gold Coast. Since 2015 there has been a divergence with the state-based Queensland Labor government moving back into the climate change adaptation space but the national Coalition government still refusing to act. The science is clear: climate change is happening, the impacts are serious, and low-lying coastal settlements like the Gold Coast are highly vulnerable to its effects. The constant policy and planning reversals over the last decade, however, have made consistent long-term planning and investment in building resilience very difficult.
Keywords: climate change adaptation; resilience; policy reversals; Gold Coast